2019
DOI: 10.3390/molecules24203716
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Development of Fluorescent Probes for Thiophenol

Abstract: Thiophenol (PhSH) belongs to a class of highly reactive and toxic aromatic thiols with widespread applications in the chemical industry for preparing pesticides, polymers, and pharmaceuticals. In this review, we comprehensively summarize recent progress in the development of fluorescent probes for detecting and imaging PhSH. These probes are classified according to recognition moieties and are detailed on the basis of their structures and sensing performances. In addition, prospects for future research are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 160 publications
0
8
0
Order By: Relevance
“…However, it is known that reactions with thiophenols can lead to fluorescence activation or deactivation and the displacement of the maximum emission wavelength. Hao et al (2019) 26 discussed studies involving sensor development, reporting that several probes with fluorescent emission wavelengths ranging from 403 to 670 nm occurred from their interaction with different types of thiophenols. Figure 4 compares the emission intensities for all compounds studied, considering the longer excitation wavelength shown in Table 4.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, it is known that reactions with thiophenols can lead to fluorescence activation or deactivation and the displacement of the maximum emission wavelength. Hao et al (2019) 26 discussed studies involving sensor development, reporting that several probes with fluorescent emission wavelengths ranging from 403 to 670 nm occurred from their interaction with different types of thiophenols. Figure 4 compares the emission intensities for all compounds studied, considering the longer excitation wavelength shown in Table 4.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The performance of conjugated polymer sensors in solution has been wellestablished, and even greater performance has been observed in solid-state sensors (Joly et al, 2006) and in aggregated polymer nanoparticles (Ahmed et al, 2013); through the use of lasers (Rose et al, 2005) for targeted two-photon excitation (Goswami et al, 2020); through the incorporation of fluorescent polymers into sensor arrays for accurate analyte identification (Tropp et al, 2020); and through the inclusion of conjugated polymers as components of carbon nanotube-based sensors (Vu et al, 2020). The use of fluorescent polymers for pesticide detection has been reported by a number of research groups (Hao et al, 2019), in many cases relying on the ability of pesticides to act as fluorescence quenchers. In one example, Zhang et al reported that a carbazole-containing polymer with significant inherent porosity was able to bind six pesticides in its porous structure, with the magnitude of fluorescence quenching different for each pesticide investigated (Figure 3A) (Zhang et al, 2020a).…”
Section: Fluorescent Polymer-based Pesticide Detectionmentioning
confidence: 99%
“…The group of Guo tried to visualize mitochondrial thiophenols and their induced oxidative stress process in live-cells, via a rationally designed rhodol-based probe [ 226 ]. Thiophenols are among the most poisonous compounds among environmental toxic substances [ 227 , 228 ]. Since mitochondria are the preferential targets for thiophenols, they are linked to pathogenic ROS production [ 229 ].…”
Section: Applicationsmentioning
confidence: 99%